Obtaining doubled haploids of Cucurbita pepo L. - E. A. Domblides; A. S. Ermolaev; S. N. Belov (Овощи России, 2021)
Doubled haploids have been widely used worldwide in breeding programs and fundamental research as valuable homozygous material for about 100 years. The species Cucurbita pepo L. are represented by a huge variety of forms, include highly productive vegetable crops and have a wide distribution in the world. Despite the great economic importance, the creation of effective protocols to ensure stable production of doubled haploids in this species remains an urgent task. DH plants are of interest not only because of the acceleration of the breeding process, but also because of the realization of the huge potential of gametoclonal variability inherent in this highly polymorphic species. In this review, we analyzed the main technologies used for obtaining doubled haploids in vegetable crops of C. pepo: parthenogenesis in situ stimulated by treated/irradiated pollen, gynogenesis in vitro (unpollinated ovule culture in vitro) and androgenesis in vitro (anther/microspore culture in vitro). An analysis is presented of the research carried out from the beginning of the discovery of haploid plants to the current advances and evaluation of the prospects in the field of DH plant production. The main critical factors influencing the efficiency of each technology and its individual steps are considered. The developed technology of doubled haploids obtaining using non-pollinated ovary culture in vitro is presented. This technology allows to obtain up to 55 embryoids per one cultivated ovary (28 embryoids/ 100 cultivated ovules) To introduce haploid technologies into the breeding process it is necessary to evaluate the obtained plants for ploidy level. The use of direct counting of chromosomes in apical cells may present a certain difficulty in this species due to their large number (2n=40) and their small size. Depending on the level of laboratory equipment, ploidy determination using flow cytometry of cell nuclei and counting the number of chloroplasts in stomatal guard cells in the epidermis of the abaxial side of the leaf may be more convenient methods. The prospects for the use of molecular markers for assessment for homozygosity in DH technologies used, including C. pepo, are discussed in the review.